Does participation mediate the prospective relationships of impairment, injury severity, and pain to quality of life following burn injury?. (October 2016) - Elliott, Timothy R; Berry, Jack W; Nguyen, Huynh Mai; Williamson, Meredith LC; Kalpinski, Ryan J; Underhill, Andrea T; Fine, Philip R
We examined the prospective impact of injury severity, functional impairment, and pain on participation in the community and subsequently on life satisfaction and self-rated health of 260 burn survivors 5 years post-discharge. Predictor variables include injury severity and total body surface area burned (assessed during acute care), functional independence (assessed at 12 months post-discharge), pain (assessed at the 24th month), and participation (assessed at the 48th month). Participation predicted life satisfaction and self-rated health. Functional independence and injury severity had significant indirect influences on adjustment via their influence on participation. Pain predicted both outcome variables. Clinical and research implications are discussed.